Water Molecular Dynamics During Dough Heating by Fast Field Cycling Nuclear Magnetic Resonance - Rondeau-Mouro, Corinne (Magnetic resonance in chemistry : MRC, 2025)
© 2025 The Author(s). Magnetic Resonance in Chemistry published by John Wiley & Sons Ltd.